The impact of digital learning on Saudi nursing students' engagement: A qualitative study - Dalyal Nader Al‐Osaimi (Wiley, 2024)
Abstract Aim This study aimed to explore the perception of nursing students regarding their engagement in digital learning environments. Design At one of universities in Saudi Arabia, a qualitative descriptive study design was used among nursing students from various academic levels. Methods Data were collected using focus group discussions among a sample of 23 participants. Data were analysed using thematic analysis. The COREQ Standards for Reporting Qualitative Research were used to report this study. Results While sharing their perceptions the nursing students reflected on the behavioural and cognitive aspects of engagement, yet they did not include emotional aspects of engagement in their conceptualization. However, the results showed that, while they reflected on their experiences they tended to reflect on emotional aspects of engagement. According to the study's results, self‐paced studying, reflective exercises, and interaction with audiovisual and dynamic content all encourage the activation of past knowledge in online learning. The learning modality also was found to be a safe and convenient approach among the participating students. Digital learning presents as a promising educational approach that extends beyond the pandemic yet, efforts should be put in place to facilitate the optimal student engagement to meet learning outcomes. Further research is needed to measure its impact on engagement and other pertinent indicators objectively.